Occupational risk of SARS-CoV-2 infection and reinfection during the second pandemic surge: a cohort study. Issue 2 (8th December 2021) - Leidi, Antonio; Berner, Amandine; Dumont, Roxane; Dubos, Richard; Koegler, Flora; Piumatti, Giovanni; Vuilleumier, Nicolas; Kaiser, Laurent; Balavoine, Jean-François; Trono, Didier; Pittet, Didier; Chappuis, François; et al.
Abstract : Objectives: This cohort study including essential workers, assessed the risk and incidence of SARS-CoV-2 infection during the second surge of COVID-19 according to baseline serostatus and occupational sector. Methods: Essential workers were selected from a seroprevalence survey cohort in Geneva, Switzerland and were linked to a state centralised registry compiling SARS-CoV-2 infections. Primary outcome was the incidence of virologically confirmed infections from serological assessment (between May and September 2020) to 25 January 2021, according to baseline antibody status and stratified by three predefined occupational groups (occupations requiring sustained physical proximity, involving brief regular contact or others). Results: 10 457 essential workers were included (occupations requiring sustained physical proximity accounted for 3057 individuals, those involving regular brief contact, 3645 and 3755 workers were classified under 'Other essential occupations'). After a follow-up period of over 27 weeks, 5 (0.6%) seropositive and 830 (8.5%) seronegative individuals had a positive SARS-CoV-2 test, with an incidence rate of 0.2 (95% CI 0.1 to 0.6) and 3.2 (95% CI 2.9 to 3.4) cases per person-week, respectively. Incidences were similar across occupational groups. Seropositive essential workers had a 93% reduction in the hazard (HR of 0.07, 95% CI 0.03 to 0.17) of having a positive test during the follow-up with no significant between-occupational group difference. Conclusions: A 10-fold reduction in the hazard of being virologically tested positive was observed among anti-SARS-CoV-2 seropositive essential workers regardless of their sector of occupation, confirming the seroprotective effect of a previous SARS-CoV2 exposure at least 6 months after infection.